PENGEMBANGAN KEILMUAN SANTRI MELALUI SELEKSI AKTIVIS BAHTSUL MASAIL DI MADRASAH HIDAYATUL MUBTADIIN LIRBOYO KEDIRI - Makhfud, Makhfud; Asyuari, A. Zaeini Misbaahuddin (ANDRAGOGI, 2023)
This article aims to discuss the scientific development of santri through the selection of Bahtsul Masail activists at Madrasah Hidayatul Mubtadiin Lirboyo Kediri. This research is qualitative research type. Data were collected through structured interviews and analyzed with descriptive analysis techniques. In this study, the results obtained are: The form of implementation of Bahtsul Masail activist selection in Hidayatul Mubtadiin Lirboyo Madrasah is through various deliberation forums and Bahtsul Masail. The results of the selection of Bahtsul Masail activists are carried out through several stages: First, recruiting Bahtsul Masail activists through special programs of Lajnah Bahtsul Masail such as the implementation of sorogan, takhasus and musyawaroh forums. Second, recruiting grade-level Bahtsul Masail activists through the kubro musyawaroh program (Muskub), combined musyawaroh (Musgab) for Tsanawiyah level students. Fathul Qorib and Al-Mahalli musyawaroh programs for Aliyah level students. Third, recruiting Bahtsul Masail activists through Bahtsul Masail at the cottage level. The implementation of the selection of Bahtsul Masail activists on the scientific development of students has a positive impact, including training public speaking, analyzing problems, utilizing self-potential from the works of previous scholars and training critical thinking intelligence.